Ergogenic drugs in sports - Knopp, W. D.; Wang, T,W.; Bach, B. R. (Clinics in Sports Medicine, 1997)
This article provides the practicing physician with an account of the commonly used ergogenic substances. Specific agents discussed include the following: stimulants, narcotic analgesics, anabolic-androgenic steroids, beta-blockers, diuretics, growth hormone, other peptide hormones, blood doping, and erythropoietin.